(untitled) (Sains Humanika, 2025)
The mental strain of the main caregivers (who are often the mothers) of children with special needs is well documented. However, the challenges of mothers who support a child with dyslexia when resources are scarce and the spouse’s presence is intermittent are less understood. Particularly, pseudo-single parenting is increasing in Johor Bahru, Malaysia due to its proximity to neighbouring Singapore and the attraction of the Singaporean currency. This phenomenon refers to families in which one parent assumes the primary role of parenting and caregiving, in the physical absence of the spouse. To understand the experiences of mothers who are left behind, a qualitative study was conducted to explore their challenges. Two mothers volunteered to share their stories, despite the stigma and sensitivity of this subject matter. The themes that emerged from the findings of the study have shown that the mothers’ emotional struggles are constantly confronted by the uncertainties in educational support and interventions; stigma due to cultural factors; low awareness and delayed intervention; the struggle of juggling multiple responsibilities; interruption in career progression and long waiting period to seek relevant expertise in the government hospitals. Although the findings have shed light on how the support system can perpetuate the struggles of these mothers, it cannot be generalized to all mothers. Particularly, variations among the mothers, according to educational levels, resources, geographical contexts, and cultural backgrounds, should be taken into consideration. Future research could further explore the experiences across various geographical locations in Malaysia to increase generalisability of the findings. The implication of this study has shown that support for families should be multipronged and multisystemic to address these struggles.